Zuhuri impirialismi Iran dar mantaqah va tahlili bar ravabiti Iran va Iraq : (Sazmani Mujahidini Khalqi Iran)
The emergence of the Iranian imperialism in the region and an analysis of Iran and Iraq relations, with and introduction and notes to the third print.